Gradient column crystal electromagnetic wire conductor and preparation method thereof

Through the electromagnetic wire conductor with gradient column crystal structure, fiber structure is formed by single-pass drawing and continuous annealing process, and then through directional heat treatment, the problem of low conductivity of existing electromagnetic wire conductors is solved, achieving high conductivity and low heat loss The effect of the product is suitable for industrial production.

CN119144800AActive Publication Date: 2024-12-17NANJING UNIV OF SCI & TECH +1

Patent Information

Application Number
CN202411283955.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-17
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

The current electromagnetic wire conductor has low conductivity, resulting in high heat loss and low energy utilization. The single crystal copper conductor preparation process is complex and costly, making it difficult to produce on industrial scale.

Method used

The electromagnetic wire conductor with gradient column crystal structure is used to form fiber structure through single-pass drawing and continuous annealing processes, and then the grains are controlled to grow in the axial direction through directional heat treatment, reducing the transverse grain boundaries and achieving high conductivity of the conductor.

Benefits of technology

The conductivity of electromagnetic wire conductors is improved to 103% IACS, and heat loss is reduced, the preparation process is simplified, and it is suitable for industrial scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144800A_ABST
    Figure CN119144800A_ABST
Patent Text Reader

Abstract

The invention provides a gradient column crystal electromagnetic wire conductor and a preparation method thereof. According to the gradient column crystal electromagnetic wire conductor, the surface layer in the cross section direction of the conductor is of a coarse grain structure, the core part is of a fine grain structure, and the conductor is of a column crystal structure in the axial direction. The method comprises the following steps: firstly, adopting drawing and continuous annealing processes, and controlling drawing deformation, annealing temperature and heating time to enable recrystallization degrees of a surface layer and a core part to be different, so as to obtain a gradient crystal electromagnetic wire conductor; and then a directional heat treatment process is adopted, the drawing rate and the temperature gradient are controlled to enable the crystal to directionally migrate, and finally the gradient column crystal electromagnetic wire conductor is obtained. The gradient column crystal electromagnetic wire conductor is prepared for the first time, the special gradient column crystal structure can reduce electron scattering and relieve the skin effect, the conductivity of the copper conductor is improved to 103% IACS, the ductility is improved to 42%, and the preparation method can produce the high-power low-loss electromagnetic wire conductor and is applied to a process assembly line.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material processing, and in particular relates to a gradient columnar crystal electromagnetic wire conductor and a preparation method thereof. Background Art

[0002] Electromagnetic wire is the "heart" of special high-end motors and transformers, and is widely used in high-voltage transmission and transformation grids, ship electromagnetic catapults, weapon launches, energy generation, rail transportation, etc. Conductivity is the core indicator of electromagnetic wire, which directly affects the performance and efficiency of electromagnetic wire.

[0003] The conductivity of electromagnetic wire conductors is determined by the material structure. The transverse grain boundaries in the material structure that are perpendicular to the current direction will scatter electrons, thereby reducing the conductivity. In addition, when the conductor is subjected to alternating current, there is a skin effect, and the current is concentrated on the surface of the conductor, thereby increasing the effective resistance and deteriorating the conductivity. According to Joule's law, the lower the conductivity, the higher the resistance and the more heat loss. Therefore, improving the conductivity of electromagnetic wire conductors is of great significance to reducing heat loss and improving energy utilization.

[0004] Taking copper conductors as an example, equiaxed copper conductors produced from low-oxygen or oxygen-free copper rod billets are widely used, and the conductivity has not been improved. In addition, single-crystal copper conductors have good conductivity, but the diameter of single-crystal copper billets is large, and they must be drawn multiple times to reach the final diameter. Drawing will increase crystal defects such as deformation twins in single-crystal copper, and intermediate annealing treatment is required. However, annealing above 400°C will produce recrystallization, and the grain boundaries will significantly reduce the conductivity. In addition, single-crystal copper is limited in length due to its special preparation process.

[0005] Based on the above reasons, there is an urgent need to develop a new structure of high conductivity electromagnetic wire conductor and its preparation method to optimize the electromagnetic wire design, reduce costs and reduce energy loss. Summary of the invention

[0006] The object of the present invention is to provide a gradient columnar crystal electromagnetic wire conductor and a preparation method thereof, so as to reduce electron scattering and alleviate skin effect, and realize the manufacture of high conductivity electromagnetic wire conductor.

[0007] A gradient columnar crystal electromagnetic wire conductor, starting from the center of the conductor circle, has a grain size that changes from fine grains to coarse grains in a gradient from the inside to the outside along the conductor cross section, and has a columnar crystal structure along the axial direction of the conductor.

[0008] Preferably, the electromagnetic wire conductor is divided into a surface tissue and a core tissue along its cross-section, the interface between the surface tissue and the core tissue is defined by a circle, the center of the circle is the center of the conductor, and the radius of the circle where the core tissue is located is 30-70% of the radius of the electromagnetic wire conductor.

[0009] Preferably, the average grain size of the surface structure is 20-200 μm, the average grain size of the core structure is 2-20 μm, and the maximum aspect ratio of the columnar crystals is 2-7.

[0010] The method for preparing the gradient columnar crystal electromagnetic wire conductor specifically comprises the following steps:

[0011] Step 1: single-pass drawing of the electromagnetic wire blank;

[0012] Step 2: Repeat the single-pass drawing of step 1 until the electromagnetic wire conductor of the required diameter is obtained;

[0013] Step 3: Continuously annealing the electromagnetic wire conductor obtained in step 2 to obtain a gradient crystal electromagnetic wire conductor;

[0014] Step 4: performing directional heat treatment on the gradient crystal electromagnetic wire conductor obtained in step 3;

[0015] Step 5: Repeat step 4 until a gradient columnar crystal electromagnetic wire conductor is obtained.

[0016] Preferably, in step 1, the electromagnetic wire blank is made of a copper rod or an electrical round aluminum rod, and the deformation amount of a single drawing pass is between 20% and 40%.

[0017] Preferably, in step 2, the single-pass drawing of step 1 is repeated 5 to 20 times.

[0018] Preferably, in step three, when continuous annealing is performed, the annealing temperature is 500-800° C., the heating time is 1-10 seconds, the protective gas is air or argon, and the cooling method is air cooling or water cooling.

[0019] Preferably, in step 4, when the directional heat treatment is performed, the temperature of the hot end area is 700-800°C, the temperature of the cold end area is room temperature, the length of the hot zone is 30-50 mm, and the pulling rate of the electromagnetic wire conductor is 5-20 mm / s.

[0020] Preferably, in step 5, the number of repetitions is 1 to 3 times.

[0021] Compared with the prior art, the present invention has the following significant advantages:

[0022] Through the technical solution of the present invention, a gradient columnar crystal structure electromagnetic wire conductor is obtained for the first time, the electrical conductivity of the copper conductor is increased to 103% IACS, and the elongation is increased to 42%; the preparation method can be applied to the process line and used for industrial-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a schematic diagram of how the gradient columnar crystal structure of the gradient columnar crystal electromagnetic wire conductor of the present invention reduces electron scattering and alleviates the skin effect.

[0024] Figure 2 The figure shows a comparison between the structure of the gradient columnar crystal electromagnetic wire conductor (a) of the present invention and the structure of the traditional electromagnetic wire conductor (b). DETAILED DESCRIPTION

[0025] The present invention is further described in detail below in conjunction with the embodiments and drawings.

[0026] Combination Figure 1 The principle of the present invention is: firstly, a single-pass drawing and continuous annealing process is adopted, wherein the grains in the conductor structure are deformed and elongated to form a fibrous structure during the drawing process. The deformation process generates residual stress and lattice distortion to store energy, providing a driving force for the subsequent recrystallization process; the subsequent continuous annealing causes recrystallization, and new grains nucleate and grow to replace the original deformed grains. The surface temperature of the conductor is high and the heating time is long, while the core temperature is low and the heating time is short. According to the recrystallization and grain growth dynamics, the higher the temperature and the longer the time, the larger the recrystallized grains. By controlling the deformation amount, continuous annealing temperature and heating time, a gradient crystal electromagnetic wire conductor is obtained. Then, a directional heat treatment process is adopted to control the pulling rate and temperature gradient, so that the grains grow axially in a directional manner during the recrystallization process, the grain boundaries migrate in a directional manner, and the lateral grain boundaries become fewer and fewer, and finally a gradient columnar crystal electromagnetic wire conductor is obtained.

[0027] Example 1

[0028] The method of the present invention specifically comprises the following steps:

[0029] Step 1: single-pass drawing of a low-oxygen copper rod electromagnetic wire blank with a diameter of 8 mm and a grade of T1M20, with a deformation of 30%;

[0030] Step 2: Repeat step 1 10 times to obtain an electromagnetic wire conductor with a diameter of 1 mm;

[0031] Step 3: Continuously annealing the electromagnetic wire conductor obtained in step 2 at a temperature of 800° C., a heating time of 1 second, an argon protective gas, and a water cooling method to obtain a gradient crystal electromagnetic wire conductor;

[0032] Step 4: Perform directional heat treatment on the gradient crystal electromagnetic wire conductor obtained in step 3, the temperature of the hot end area is controlled at 750°C, the temperature of the cold end area is controlled at about room temperature, the length of the hot zone is 40mm, and the pulling rate of the electromagnetic wire conductor is 15mm / s;

[0033] Step 5: Repeat step 4 once to obtain a gradient columnar crystal electromagnetic wire conductor. SEM Figure 2 As shown in a, it is different from the organization of traditional electromagnetic wire conductors ( Figure 2 Compared with b), the average grain size of the fine grain structure in the core of the gradient columnar crystal electromagnetic wire conductor prepared in this embodiment is 2 μm, the average grain size of the coarse grain structure on the surface is 200 μm, and the maximum aspect ratio of the columnar crystal is 7.

[0034] According to tests, the conductivity of the copper conductor of the electromagnetic wire is increased to 103% IACS, and the elongation is increased to 42%; the preparation method can be applied to the process line and used for industrial-scale production.

[0035] Example 2

[0036] The method of the present invention specifically comprises the following steps:

[0037] Step 1: single-pass drawing of a low-oxygen copper rod electromagnetic wire blank with a diameter of 8 mm and a grade of T1M20, with a deformation of 30%;

[0038] Step 2: Repeat step 1 10 times to obtain an electromagnetic wire conductor with a diameter of 1 mm;

[0039] Step 3: Continuously annealing the electromagnetic wire conductor obtained in step 2 at a temperature of 500° C., a heating time of 1 second, an argon protective gas, and a water cooling method to obtain a gradient crystal electromagnetic wire conductor;

[0040] Step 4: Perform directional heat treatment on the gradient crystal electromagnetic wire conductor obtained in step 3, the temperature of the hot end area is controlled at 750°C, the temperature of the cold end area is controlled at about room temperature, the length of the hot zone is 40mm, and the pulling rate of the electromagnetic wire conductor is 15mm / s;

[0041] Step 5: Repeat step 4 once to obtain a gradient columnar crystal electromagnetic wire conductor, the average grain size of the core fine crystal structure is 2 μm, the average grain size of the surface coarse crystal structure is 20 μm, and the maximum aspect ratio of the columnar crystal is 7. The conductivity of the electromagnetic wire copper conductor is increased to 101.5% IACS, and the elongation is increased to 44%.

[0042] Example 3

[0043] The method of the present invention specifically comprises the following steps:

[0044] Step 1: single-pass drawing of a low-oxygen copper rod electromagnetic wire blank with a diameter of 8 mm and a grade of T1M20, with a deformation of 30%;

[0045] Step 2: Repeat step 1 10 times to obtain an electromagnetic wire conductor with a diameter of 1 mm;

[0046] Step 3: Continuously annealing the electromagnetic wire conductor obtained in step 2 at a temperature of 800° C., a heating time of 10 seconds, an argon protective gas, and a water cooling method to obtain a gradient crystal electromagnetic wire conductor;

[0047] Step 4: Perform directional heat treatment on the gradient crystal electromagnetic wire conductor obtained in step 3, the temperature of the hot end area is controlled at 750°C, the temperature of the cold end area is controlled at about room temperature, the length of the hot zone is 40mm, and the pulling rate of the electromagnetic wire conductor is 15mm / s;

[0048] Step 5: Repeat step 4 once to obtain a gradient columnar crystal electromagnetic wire conductor, the average grain size of the core fine grain structure is 20 μm, the average grain size of the surface coarse grain structure is 200 μm, and the maximum aspect ratio of the columnar crystal is 7. The conductivity of the electromagnetic wire copper conductor is increased to 102.4% IACS, and the elongation is increased to 35%.

[0049] Example 4

[0050] The method of the present invention specifically comprises the following steps:

[0051] Step 1: single-pass drawing of a low-oxygen copper rod electromagnetic wire blank with a diameter of 8 mm and a grade of T1M20, with a deformation of 30%;

[0052] Step 2: Repeat step 1 10 times to obtain an electromagnetic wire conductor with a diameter of 1 mm;

[0053] Step 3: Continuously annealing the electromagnetic wire conductor obtained in step 2 at a temperature of 800° C., a heating time of 1 second, an argon protective gas, and a water cooling method to obtain a gradient crystal electromagnetic wire conductor;

[0054] Step 4: Perform directional heat treatment on the gradient crystal electromagnetic wire conductor obtained in step 3, the temperature of the hot end area is controlled at 750°C, the temperature of the cold end area is controlled at about room temperature, the length of the hot zone is 40mm, and the pulling rate of the electromagnetic wire conductor is 5mm / s;

[0055] Step 5: Repeat step 4 once to obtain a gradient columnar crystal electromagnetic wire conductor, the average grain size of the core fine grain structure is 2 μm, the average grain size of the surface coarse grain structure is 200 μm, and the maximum aspect ratio of the columnar crystal is 2. The conductivity of the electromagnetic wire copper conductor is increased to 102% IACS, and the elongation is increased to 41%.

[0056] Example 5

[0057] The method of the present invention specifically comprises the following steps:

[0058] Step 1: single-pass drawing of a low-oxygen copper rod electromagnetic wire blank with a diameter of 8 mm and a grade of T1M20, with a deformation of 30%;

[0059] Step 2: Repeat step 1 10 times to obtain an electromagnetic wire conductor with a diameter of 1 mm;

[0060] Step 3: Continuously annealing the electromagnetic wire conductor obtained in step 2 at a temperature of 800° C., a heating time of 1 second, an argon protective gas, and a water cooling method to obtain a gradient crystal electromagnetic wire conductor;

[0061] Step 4: Perform directional heat treatment on the gradient crystal electromagnetic wire conductor obtained in step 3, the temperature of the hot end area is controlled at 750°C, the temperature of the cold end area is controlled at about room temperature, the length of the hot zone is 40mm, and the pulling rate of the electromagnetic wire conductor is 20mm / s;

[0062] Step 5: Repeat step 4 once to obtain a gradient columnar crystal electromagnetic wire conductor, the average grain size of the core fine grain structure is 2 μm, the average grain size of the surface coarse grain structure is 200 μm, and the maximum aspect ratio of the columnar crystal is 5. The conductivity of the electromagnetic wire copper conductor is increased to 102.6% IACS, and the elongation is increased to 42%.

[0063] Comparative Example 1

[0064] The method of the present invention specifically comprises the following steps:

[0065] Step 1: single-pass drawing of a low-oxygen copper rod electromagnetic wire blank with a diameter of 8 mm and a grade of T1M20, with a deformation of 30%;

[0066] Step 2: Continuously annealing the electromagnetic wire blank after drawing in step 1, the temperature is 800° C., the heating time is 20 seconds, the protective gas is argon, and the cooling method is water cooling;

[0067] Step 3: Repeat steps 1 to 2 10 times to obtain a gradient crystal electromagnetic wire conductor with a diameter of 1 mm;

[0068] Step 4: performing directional heat treatment on the gradient crystal electromagnetic wire conductor obtained in step 3, with a regional heating temperature of 750° C., a hot zone length of 40 mm, and an electromagnetic wire conductor pulling rate of 15 mm / s;

[0069] Step 5: Repeat step 4 once to obtain an electromagnetic wire conductor, the average grain size of the core fine grain structure is 50 μm, the average grain size of the surface coarse grain structure is 200 μm, and the maximum aspect ratio of the columnar crystal is 7. The core fine grain structure is too large, the conductivity of the electromagnetic wire copper conductor is 102.5% IACS, and the elongation is reduced to 29%.

[0070] Comparative Example 2

[0071] The method of the present invention specifically comprises the following steps:

[0072] Step 1: single-pass drawing of a low-oxygen copper rod electromagnetic wire blank with a diameter of 8 mm and a grade of T1M20, with a deformation of 30%;

[0073] Step 2: Continuously annealing the electromagnetic wire blank after drawing in step 1, the temperature is 500° C., the heating time is 0.5 s, the protective gas is argon, and the cooling method is water cooling;

[0074] Step 3: Repeat steps 1 to 2 10 times to obtain a gradient crystal electromagnetic wire conductor with a diameter of 1 mm;

[0075] Step 4: performing directional heat treatment on the gradient crystal electromagnetic wire conductor obtained in step 3, with a regional heating temperature of 750° C., a hot zone length of 40 mm, and an electromagnetic wire conductor pulling rate of 15 mm / s;

[0076] Step 5: Repeat step 4 once to obtain an electromagnetic wire conductor, the average grain size of the core fine grain structure is 2 μm, the average grain size of the surface coarse grain structure is 5 μm, and the maximum aspect ratio of the columnar crystal is 7. The surface coarse grain structure is too small, and the conductivity of the electromagnetic wire copper conductor is reduced to 98.7% IACS and the elongation is 44%.

[0077] Comparative Example 3

[0078] The method of the present invention specifically comprises the following steps:

[0079] Step 1: single-pass drawing of a low-oxygen copper rod electromagnetic wire blank with a diameter of 8 mm and a grade of T1M20, with a deformation of 30%;

[0080] Step 2: Continuously annealing the electromagnetic wire blank after drawing in step 1, the temperature is 800° C., the heating time is 1 second, the protective gas is argon, and the cooling method is water cooling;

[0081] Step 3: Repeat steps 1 to 2 10 times to obtain a gradient crystal electromagnetic wire conductor with a diameter of 1 mm;

[0082] Step 4: performing directional heat treatment on the gradient crystal electromagnetic wire conductor obtained in step 3, with a regional heating temperature of 750° C., a hot zone length of 40 mm, and an electromagnetic wire conductor pulling rate of 3 mm / s;

[0083] Step 5: Repeat step 4 3 times to obtain an electromagnetic wire conductor, the average grain size of the core fine grain structure is 2μm, the average grain size of the surface coarse grain structure is 200μm, the maximum aspect ratio of the columnar crystal is 1, and it is equiaxed. The conductivity of the electromagnetic wire copper conductor is reduced to 100% IACS and the elongation is 42%.

[0084] Comparative Example 4

[0085] The method of the present invention specifically comprises the following steps:

[0086] Step 1: single-pass drawing of a low-oxygen copper rod electromagnetic wire blank with a diameter of 8 mm and a grade of T1M20, with a deformation of 30%;

[0087] Step 2: Continuously annealing the electromagnetic wire blank after drawing in step 1, the temperature is 800° C., the heating time is 1 second, the protective gas is argon, and the cooling method is water cooling;

[0088] Step 3: Repeat steps 1 to 2 10 times to obtain a gradient crystal electromagnetic wire conductor with a diameter of 1 mm;

[0089] Step 4: performing directional heat treatment on the gradient crystal electromagnetic wire conductor obtained in step 3, with a regional heating temperature of 750° C., a hot zone length of 40 mm, and an electromagnetic wire conductor pulling rate of 45 mm / s;

[0090] Step 5: Repeat step 4 3 times to obtain an electromagnetic wire conductor, the average grain size of the core fine grain structure is 2μm, the average grain size of the surface coarse grain structure is 200μm, the maximum aspect ratio of the columnar crystal is 1, and it is equiaxed. The conductivity of the electromagnetic wire copper conductor is reduced to 100% IACS and the elongation is 42%.

Claims

1. A gradient columnar crystal electromagnetic wire conductor, It is characterized in that Starting from the center of the conductor, along the cross-section of the conductor from the inside to the outside, the grain size changes gradually from fine grains to coarse grains, and along the axial direction of the conductor is a columnar crystal structure.

2. The gradient columnar crystal electromagnetic wire conductor according to claim 1, It is characterized in that The electromagnetic wire conductor is divided into a surface tissue and a core tissue along its cross-sectional direction. The interface between the surface tissue and the core tissue is defined by a circle, the center of the circle is the center of the conductor, and the radius of the circle where the core tissue is located is 30-70% of the radius of the electromagnetic wire conductor.

3. The gradient columnar crystal electromagnetic wire conductor according to claim 1, It is characterized in that The average grain size of the surface structure is 20~200μm, the average grain size of the core structure is 2~20μm, and the maximum aspect ratio of the columnar crystal is 2~7.

4. The method for preparing the gradient columnar crystal electromagnetic wire conductor according to any one of claims 1 to 3, It is characterized in that The following steps are involved: Step 1: single-pass drawing of the electromagnetic wire blank; Step 2: Repeat the single-pass drawing of step 1 until the electromagnetic wire conductor of the required diameter is obtained; Step 3: Continuously annealing the electromagnetic wire conductor obtained in step 2 to obtain a gradient crystal electromagnetic wire conductor; Step 4: performing directional heat treatment on the gradient crystal electromagnetic wire conductor obtained in step 3; Step 5: Repeat step 4 until a gradient columnar crystal electromagnetic wire conductor is obtained.

5. The method according to claim 4, It is characterized in that In step 1, the electromagnetic wire blank is made of copper rod or electrical round aluminum rod, and the single-pass drawing deformation is between 20% and 40%.

6. The method according to claim 4, It is characterized in that In step 2, the single-pass drawing of step 1 is repeated 5 to 20 times.

7. The method according to claim 4, It is characterized in that In step three, when continuous annealing is performed, the annealing temperature is 500-800° C., the heating time is 1-10 seconds, the protective gas is air or argon, and the cooling method is air cooling or water cooling.

8. The method according to claim 4, It is characterized in that In step 4, when directional heat treatment is performed, the temperature of the hot end area is 700~800°C, the temperature of the cold end area is room temperature, the length of the hot zone is 30~50mm, and the pulling rate of the electromagnetic wire conductor is 5~20mm / s.

9. The method according to claim 4, It is characterized in that In step 5, repeat 1 to 3 times.

Citation Information

Patent Citations

  • Method for constructing coarse grain-fine grain gradient structure on surface of metal material and gradient structure

    CN105821180A

  • Gradient metal material with coarse grains on surface layer and nano grains or ultra-fine grains inside and preparing method

    CN110172655A

  • Method for eliminating transverse grain boundary in high-conductivity pure copper wire

    CN111118421A

  • Method for preparing gradient nanostructure on end face of metal material rotating part

    CN115971788A

  • Copper target thermomechanical treatment process suitable for continuous production

    CN117305739A

Cited By

  • Low-resistivity gradient crystal wire and preparation method thereof

    CN119144795A

  • A low resistivity gradient crystal wire and its preparation method

    CN119144795B